2020
DOI: 10.1101/2020.04.01.20050526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meteorological factors correlate with transmission of 2019-nCoV: Proof of incidence of novel coronavirus pneumonia in Hubei Province, China

Abstract: Objective: many potential factors contribute to the outbreak of COVID-19. The aim of this study was to explore the effects of various meteorological factors on the incidence of COVID-19. Methods:Taking Hubei province of China as an example, where COVID-19 was first reported and there were the most cases, we collected 53 days of cases up to March 10(total 67773 confirmed cases).COVID-19 confirmed cases were retrieved from the official website of Hubei Health Commission. Ten meteorological parameters were provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
1
8
0
1
Order By: Relevance
“…This study showed that higher AAP led to the rapid spread of COVID-19 during the early stage of the pandemic. Our results are consistent with a previous study conducted in Hubei Province of China, which demonstrated that the incidence of COVID-19 was positively correlated with AAP 15 ; however, our results are in contrast with other studies conducted in Japan 16 and China 17 . Use of a larger dataset than in those previous studies and systematic approaches may lead to more robust conclusions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed that higher AAP led to the rapid spread of COVID-19 during the early stage of the pandemic. Our results are consistent with a previous study conducted in Hubei Province of China, which demonstrated that the incidence of COVID-19 was positively correlated with AAP 15 ; however, our results are in contrast with other studies conducted in Japan 16 and China 17 . Use of a larger dataset than in those previous studies and systematic approaches may lead to more robust conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…The underlying mechanism behind the relationship of AAP with the transmission of COVID-19 is unclear. One explanation might be that increased AAP may lead to an increase in the number of viruses per unit area when the human body expels respiratory viruses 15 . A positive correlation was observed between COVID-19 transmission and PD, consistent with previous study 20 , which also strengthens the notion that lockdown policies can help to atten the epidemic curve 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis of data from 16 Chinese provinces concluded that RH and SARS-CoV-2 transmission rates have no significant spatial correlation (R = -0.17, p = 0.48) ( Lin et al, 2020a ). Similarly, multiple other studies did not find a significant association between RH and SARS-CoV-2 transmission in China ( Li et al, 2020b ; Metelmann et al, 2020 ; Rahman et al, 2020 ; Yao et al, 2020b ).…”
Section: Introductionmentioning
confidence: 63%
“…Out of those 14 provinces, 12 showed a negative correlation between daily temperature and the number of infected cases ( Rahman et al, 2020 ). A group of studies reported that with regression and correlation analysis, increment in temperature resulted in a decrease in the daily number of confirmed cases ( Li et al, 2020a ; Li et al, 2020b ; Liu et al, 2020b ; Luo et al, 2020 ; Rouen et al, 2020 ; Oliveiros et al, 2020 ; Qi et al, 2020 ; Xie and Zhu, 2020 ). Several other studies analyzed variables from the Susceptible-Exposed-Infectious-Recovered (SEIR) model with regression analysis and showed that the transmission rate was negatively related to temperature ( Guo et al, 2020 ; Lin et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The growth rate of COVID-19 cases peaked at a temperature of ~5°C and a humidity of 0.6 to 1 kPa in the temperate regions of the Northern Hemisphere during the outbreak month, while it decreased in regions that had warmer or colder temperatures 9 . Likewise, average pressure, average temperature, minimum temperature, and average water vapor pressure were found to be significantly correlated with the incidence of COVID-19 10,11 . Generally, the largest contiguous syndromes outbreak in the regions of cooler weather, leading to the theories that high temperatures might begin to the tail of in the summer season 1 .…”
mentioning
confidence: 87%